Plant reintroduction in restored peatlands: 80% successfully transferred – Does the remaining 20% matter? - Sandrine Hugron; Mélina Guêné-Nanchen; Noémie Roux; Marie-Claire LeBlanc; Line Rochefort (Global Ecology and Conservation, 2020)
In ecological restoration, especially in projects aiming at introducing a diverse plant community, species that do not establish are rarely reported., Yet, knowledge gained from identifying and understanding the reasons why species did not establish is useful to improve restoration techniques. In this paper, we used Sphagnum dominated peatlands restored with the Moss Layer Transfer Technique (MLTT) as a typical example of restored ecosystems for which information about species that does not establish is lacking. By comparing the plant species pools of 22 pairs of donor/restored Sphagnum peatlands (including 17 sites restored for more than 10 years), we calculated that the proportion of successfully introduced plant species (transfer rate) was 82 ± 9%, amongst the highest transfer rate when compared to other restoration projects. Only five vascular plant species were classified as recalcitrant – species present in the donor site but absent from the restored sites: Carex trisperma, Cypripedium acaule, Ilex mucronata, Maianthemum trifolium and Rubus chamaemorus. Explanations about the filters impeding establishment were mainly based on the autoecology of the species. Depending on restoration goals (e.g. return of edible berries or orchid diversity) we recommend the specific reintroduction of recalcitrant species after the MLTT.